Aplikasi Commodity System Assessment Method dalam Distribusi Sawi Putih (Brassica pekinensia L) dari Petani Di Baturiti Ke Pengecer Di Denpasar - Tampubolon, Markus Adrian; Harsojuwono, Bambang Admadi; Anggreni, A.A.M. Dewi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2023)
Napa cabbage is the fourth largest horticultural production in Bali. The potential for chicory, which is quite large, is needed by the community, which has problems that are easily damaged after harvesting and line distribution.This study aims to 1) determine the line distribution and the types line distribution of napa cabbage, 2) determine the system, the subjects, and postharvest handling of napa cabbage 3) calculating the impact of post-harvest handling of napa cabbage during distribution towards post-harvest activities from farmers in Baturiti District to retailers in Denpasar. The snowball sampling method was used to find out the types and distribution line of napa cabbage, and to analyze the system and the impact of post-harvest on each distribution lines the Commodity System Assessment Method was used with surveys and interviews directly to stakeholders. The results showed that there are four distribution lines of napa cabbage from farmers in Baturiti Distric to retailers in Denpasar, namely line 1) farmers to retailers, 2) farmers to collectors and then to retailers, 3) farmers to whosalers then to suppliers, 4) farmers to collectors then to suppliers. Post-harvest handling during the distribution includes sorting and cleaning, grading, weighing, packaging, distribution, display, and storage. The impact of handling on postharvest losses on the sorting stage at the farmer level is 10,25 percent (significant), collectors 11,42 percent (significant), wholesalers 3,16 percent (not significant), suppliers 4,55 percent (not significant) and retailers 10,68 percent (significant) .   Keywords : napa cabbage, distribution chain, CSAM, farmer of Baturiti, retailer of Denpasar Sawi putih merupakan urutan ke-empat produksi hortikultura terbesar di Bali. Potensi sawi putih yang cukup besar dibutuhkan oleh masyarakat mempunyai kendala yang mudah rusak pasca pemanenannya dan saat distribusi. Tujuan dari penelitian ini untuk 1) mengetahui jenis dan jumlah jalur distribusi sawi putih 2) menentukan sistem, pelaku, dan penanganan pascapanen sawi putih 3) menghitung dampak penanganan pascapanen sawi putih selama pendistribusian mulai dari tingkat petani di Kecamatan Baturiti hingga ke pengecer di Denpasar. Metode snowball sampling digunakan untuk mengetahui tipe dan jalur distribusi sawi putih, dan untuk menganalisis sistem dan dampak penanganan pada setiap jalur distribusi digunakan Commodity System Assessment Method dengan cara survei dan wawancara langsung ke stakeholder . Didapat hasil penelitian yaitu terdapat empat jalur distribusi sawi putih dari petani di Kecamatan Baturiti hingga ke pengecer di Denpasar yaitu, 1) petani ke pengecer, 2) petani ke pengepul lalu ke pengecer, 3) petani ke pedagang besar lalu ke supplier , 4) petani ke pengepul lalu ke supplier . Penanganan pascapanen selama jalur distribusi meliputi sortasi dan pembersihan, grading , penimbangan, pengemasan, pendistribusian, pemajangan, dan penyimpanan. Dampak penanganan terhadap kehilangan pascapanen tahap sortasi tingkat petani adalah 10,25 persen (signifikan), pengepul 11,42 persen (signifikan), pedagang besar 3,16 persen (tidak signifikan), supplier 4,55 persen (tidak signifikan) dan pengecer 10,68 persen (signifikan).   Kata kunci : sawi putih, jalur distribusi, CSAM, petani Baturiti, pengecer Denpasar